Belief in systemic racism and self-employment among working blacks. Issue 1 (2nd January 2021) - Bento, Asia; Brown, Tony N.
ABSTRACT: Scholars theorize that black–white disparities in self-employment persist because of racial disparities in human capital (e.g. educational attainment) and financial capital (e.g. assets). Such disparities represent the enduring economic legacy of racism. Yet, racism may also mobilize working blacks to pursue self-employment. In this study, we address whether working blacks' racial capital – operationalized as belief in the significance of systemic racism – predicts their self-employment status. With nationally representative survey data from the 2012 Outlook on Life Surveys ( n = 2, 294), we address the following research question: net of human capital, financial capital, and control variables, does racial capital correlate with self-employment status among working blacks? Results indicate that racial capital associates positively with self-employment status. We conclude that racism may influence how and why working blacks pursue economic mobility.